A Comprehensive Study of 2000 Narrow Line Seyfert 1 Galaxies from the Sloan Digital Sky Survey. I. The Sample - Zhou, Hongyan; Wang, Tinggui; Yuan, Weimin; Lu, Honglin; Dong, Xiaobo; Wang, Junxian; Lu, Youjun (The Astrophysical journal. Supplement series, 2006)
This is the first paper in a series dedicated to the study of the emission-line and continuum properties of narrow line Seyfert 1 galaxies (NLS1s). We carried out a systematic search for NLS1s from objects assigned as "QSOs" or "galaxies" in the spectroscopic sample of the Sloan Digital Sky Survey Data Release 3 (SDSS DR3) by a careful modeling of their emission lines and continua. The result is a uniform sample comprising 62000 NLS1s. This sample dramatically increases the number of known NLS1s by a factor of 610 over previous compilations. This paper presents the parameters of the prominent emission lines and continua, which were measured accurately with typical uncertainties <10%. Taking advantage of such an unprecedented large and uniform sample with accurately measured spectral parameters, we carried out various statistical analyses, some of which were only possible for the first time. The main results found are as follows. (1) Within the overall Seyfert 1 population, the incidence of NLS1s is strongly dependent on the optical, X-ray, and radio luminosities as well as the radio loudness. The fraction of NLS1s peaks around SDSS g-band absolute magnitude M sub(g) 6 -22 mag in the optical and 6 10 super(43.2) ergs s super(-1) in the soft X-ray band, and decreases quickly as the radio loudness increases. (2) On average the relative Fe II emission, R sub(4570) = Fe super(II) ll4434-4684/Hb, in NLS1s is about twice that in normal active galactic nuclei (AGNs) and is anticorrelated with the broad component width of the Balmer emission lines. (3) The well-known anticorrelation between the width of broad low-ionization lines and the soft X-ray spectral slope for broad line AGNs extends down to FWHM 6 1000 km s super(-1) in NLS1s, but the trend appears to reverse at still smaller line widths. (4) The equivalent width of Hb and Fe II emission lines are strongly correlated with the Hb and continuum luminosities. (5) We do not find any difference between NLS1s and normal AGNs in regard to the narrow line region. (6) We have examined the black hole mass versus stellar velocity dispersion (M sub(BH)-s*) relation for a subsample of 308 NLS1s for which s* could be measured directly from fitting the starlight in the SDSS spectra with our stellar spectral templates. A significant correlation between M sub(BH) and s* is found, but with the bulk of black hole masses falling below the values expected from the M sub(BH)-s* relation for normal galaxies and normal AGNs. This result indicates that NLS1s are underage AGNs, where the growth of the SMBH lags behind the formation of the galactic bulge. (7) We also find that the FWHM of [N II] line is well correlated with s* in 206 NLS1s, for which both parameters could be derived with reasonable accuracy. The [N II] width can predict the stellar velocity dispersion to an accuracy of 6 30%. A similar M sub(BH)-s* relation could be found for a larger sample of 613 NLS1s on making use of the more reliable measurements of FWHM[N II].